(untitled) (Revista NUPEART, 2023)
The text on screen deals with an academic elaboration developed in the Research Group on Education in the Amazon through the Line of Research Literacy and Written Culture of the Federal University of Rondônia (UNIR). The purpose was to analy- ze the results of the research project "Intercultural Literacy on Instagram: exercises of indigenous teacher training" developed from 2021 to June 2022 through bibliographic, documentary and narrative research. The results suggest that digital platforms are important in ensuring interactive communication, compliance with health protocols and the occupation of cyberspace, which in this context can represent a large place for training and deve- lopment and transfer of new technologies and innovation. We infer that the project provided a formative action on the entry of indigenous peoples into the current writing cultures through digital aesthetic possibilities, specific and differentiated.